(untitled) (Research, Society and Development, 2020)
Objective: This study was designed with the aim of pointing out the different techniques used in the diagnosis of SARS-CoV-2, reviewing the advantages and disadvantages between the serological and molecular methods, as well as the main parameters in cizânia, in addition to describing details about the contribution of imaging to the diagnostic conclusion. Methodology: It consists of a literature review article of a descriptive and exploratory nature, elaborated using content published in the Pubmed, SciELO and Google academic databases, between the years 2019 and 2020, which after careful analysis, a total of 29 articles, these, which characterized the main advantages and disadvantages of the different diagnostic tests available. Literature review: Early diagnosis of Covid-19 is essential for patient stabilization and containment of the epidemic, therefore, suspected cases can be investigated and later confirmed, through the association between laboratory tests, imaging tests and clinical investigation epidemiological. Final considerations: Laboratory tests and imaging tests have been an important tool in the diagnosis of SARS-CoV-2. The immunochromatography technique may present false negative results, which deserves specific attention, since, even if there are no positive reactions, the hypothesis of the disease in the individual cannot be ruled out, since positive reactions require specific concentrations of antibodies for its detection, which makes molecular tests, especially RT-PCR, considered a gold standard in elucidation.